MEMBENTUK KARAKTER PESERTA DIDIK MELALUI PEMBELAJARAN IPS DI MI TARBIYATUS SHIBYAN - Zahratun Naemah; Rifatul Fadhila; Veni Veronica Siregar (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This investigation expects to break down how to shape the personality of understudies through friendly examinations learning at MI Tarbiyatus Shibyan The exploration technique utilized is subjective with an enlightening methodology that is library research. In light of the information acquired, the analysts tracked down that in molding the personality of understudies through friendly investigations learning, in particular by utilizing the CTL learning strategy. This examination likewise contributes in giving a nitty gritty depiction of the use of the joining of character esteems with science to be utilized as a source of perspective for the execution of instructing and learning exercises. Furthermore, the examination is additionally done to help educators and scholastic activists so that there is no detachment between strict information and general science. Keywords : Character, IPS, Madrasah Ibtidaiyah